Study of Purpose and Objectives of Social Work - Rani, Rakhi (Innovative Research Thoughts, 2017)
The objective of “social work” is to assist those who are in need in order for them to have the ability to cope with their difficulties on their own. It is both a scientific and an artistic endeavour. It is scientific in the sense that information drawn from several disciplines provides the body of knowledge for a social worker, and sheke use this theoretical foundation to assist others, i.e., to perform what she preaches. It is necessary to put into practise what the theory suggests. Skill is defined as the ability to do the task at hand. As a result, professional social work must be converted into a professional service by incorporating chosen knowledge and a set of social work values into its practise.